2021
DOI: 10.1021/acsami.0c20837
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro and In Vivo Demonstration of Ultraefficient and Broad-Spectrum Antibacterial Agents for Photodynamic Antibacterial Chemotherapy

Abstract: Increasing threats from both pathogenic infections and antibiotic resistance highlight the pressing demand for nonantibiotic agents and alternative therapies. Herein, we report several new phenothiazinium-based derivatives, which could be readily synthesized via fragment-based assembly, which exhibited remarkable bactericidal activities both in vitro and in vivo. Importantly, in contrast to numerous clinically and preclinically used antibacterial photosensitizers, these compounds were able to eliminate various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…This result is consistent with our hypothesis that Fe 3 O 4 -GOx nanozyme with closely co-localized GOx and Fe 3 O 4 NPs can synergistically address the issues of hyperglycemia, hypoxia, oxidative stress and biofilm infection, reshaping the pathological wound microenvironment and rescuing the stalled healing in DU. Compared with photodynamic antimicrobial chemotherapy commonly used in chronic wound treatment [ 51 ], Fe 3 O 4 -GOx nanozyme exhibits comparable broad-spectrum antimicrobial performance as well as wound healing rate without the help of light irradiation, addressing the shortcomings of conventional phototherapy (e.g., limited light penetration depth, and wound hypoxia). Furthermore, apart from outstanding anti-oxidant activity similar to the commonly used anti-oxidant hydrogel [ 52 ], the Fe 3 O 4 -GOx also possessed additional pH-switchable antimicrobial capability, which makes it more suitable for DU wound treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with our hypothesis that Fe 3 O 4 -GOx nanozyme with closely co-localized GOx and Fe 3 O 4 NPs can synergistically address the issues of hyperglycemia, hypoxia, oxidative stress and biofilm infection, reshaping the pathological wound microenvironment and rescuing the stalled healing in DU. Compared with photodynamic antimicrobial chemotherapy commonly used in chronic wound treatment [ 51 ], Fe 3 O 4 -GOx nanozyme exhibits comparable broad-spectrum antimicrobial performance as well as wound healing rate without the help of light irradiation, addressing the shortcomings of conventional phototherapy (e.g., limited light penetration depth, and wound hypoxia). Furthermore, apart from outstanding anti-oxidant activity similar to the commonly used anti-oxidant hydrogel [ 52 ], the Fe 3 O 4 -GOx also possessed additional pH-switchable antimicrobial capability, which makes it more suitable for DU wound treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Since the first conjugated polymer sensor was reported in the 1990s, this sensing platform has advanced more than two decades, with an explosion of research in this sector noted in the previous 10 years [ 107 ]. For instance, water-soluble conjugated polymers with ionic side chains are known as conjugated polyelectrolytes (CPEs) [ 108 , 109 , 110 , 111 , 112 ], and they have garnered attention in the past decade mainly because of their application as sensors, energy converters, and antimicrobials [ 113 , 114 , 115 , 116 ]. For example, Tan et al [ 117 ] developed and synthesized four anionic CPEs with a poly(paraphenylene ethynylene) (PPE, Figure 14 a) backbone but varied pendant ionic side chains.…”
Section: Polymers Containing Fluorophoresmentioning
confidence: 99%
“…The misuse of antibiotics results in a rapid increase in drugresistant bacteria, which poses a tremendous threat to global health. 1,2 As a common human pathogenic bacterium, Staphylococcus aureus (S. aureus) causes a variety of diseases such as skin and soft tissue infections, endocarditis, osteomyelitis, bacteremia and fatal pneumonia. 3,4 It is reported that methicillin-resistant S. aureus (MRSA), also known as superbug, results in nearly 20 000 deaths in the United States each year.…”
Section: Introductionmentioning
confidence: 99%